Pengaruh Persepsi Tentang Advertorial Produk Kesehatan Di Koran Pada Sikap Konsumen - Rika Melati (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2018)
Advertorial is advertising looks like news as its editorial format. The purpose of advertising is to influence consumer buying behavior. Consumer attitude is one of predictor to determine consumer behavior. The purpose of this research is to analysis influence perception of health product advertorial toward consumer attitude. Method of this research is survey which Gadjah Mada University (GMU) student that have read advertorial of healt product in newspaper as population. Method of sampling use purposive sampling. There are 3 variables in this research: perception of health product advertorial as independent variable while cognitive and affective response as dependent variables. All variables are measured using Likert scale. The primary data collected using questionnaires that given to 170 respondents. Validity and reliability of research instrument were tested using Confirmatory Factor Analysis and Alpha Cronbach’s. All hypotheses tested by using Linear Regression. The finding of this research shown that perception of health product advertorial significantly influence cognitive and affective of consumer response . The influence perception of health product advertorial toward cognitive response of GMU student that read newpaper is 21,3% and the influence of health product advertorial toward affective response of GMU student that read newspaper is 8,7%. Another factors estimated influencing attitude toward the advertorial are individual education, attitude toward the brand previously, and level of individual involvement.